Fraud prevention capability and organizational culture: A case study of government agencies - Adhi Alfian, Memed Sueb, Nunuy Nur Afiah, Yayan Syatyakti, (Opción, 2019)
We performed a quantitative method with a probit, logit, and factorial analysis technique to measure the effect of organizational culture on fraud prevention indicators. The importance of the result shows that improving fraud prevention should be associated with organizational culture also financial audit practice, because financial audit practice is not guaranteed by improving fraud prevention. In conclusion, the financial audit opinion is not significant in improving fraud prevention. On the hand, it is important if the whole assumption as we did in treatment effect that improving financial audit practice improve fraud prevention index.